2017
DOI: 10.1071/rd15190
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA fragmentation in cryopreserved samples from subjects with different cancers

Abstract: Abstract. Sperm cryopreservation is widely used by cancer patients undergoing chemo-or radiotherapy. Evidence suggests that IVF outcome with cryopreserved spermatozoa from cancer patients is less successful. To determine whether sperm DNA fragmentation (SDF) is involved in the lower fertilising ability of cryopreserved spermatozoa of cancer patients, SDF was evaluated in thawed spermatozoa from 78 men affected by different cancers and 53 men with noncancer pathologies. SDF was assessed by the terminal deoxyrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In addition to the negative impact of the disease itself or oncological gonadotoxic treatment on the basic criteria of semen quality (number, motility, morphology), the negative impact of the disease is also reflected in increased sperm DNA fragmentation. 25 , 26 Meta-analyses have shown that increased sperm DNA fragmentation negatively affects IVF/ICSI outcomes even in the healthy male population. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the negative impact of the disease itself or oncological gonadotoxic treatment on the basic criteria of semen quality (number, motility, morphology), the negative impact of the disease is also reflected in increased sperm DNA fragmentation. 25 , 26 Meta-analyses have shown that increased sperm DNA fragmentation negatively affects IVF/ICSI outcomes even in the healthy male population. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a previous study from our laboratory, we demonstrated that spermatozoa from oncological patients have higher DNA damage after thawing in respect to non-cancer patients, implying a higher susceptibility to thermic shock in oncological patients. 36 In our current study, in order to obtain information on the genomic integrity of spermatozoa in the context of natural conception, we analyzed fresh semen samples at all time-points.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns were raised about the genetic integrity of spermatozoa after genotoxic treatments, especially based on the observations about the persistence of increased aneuploidy rate and DNA fragmentation in some patients up to 18/24 months 9–13 . It is well known that etoposide, a component of the BEP regimen, inhibits both topoisomerase II activity and the disjunction of recombinant chromosomes and sister chromatids, leading to aneuploidy 35,36 . On the other hand, platinum‐based drugs, that is, cisplatin and CP, and RT are known to cause DNA strand breaks.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) analysis may be used to determine the proportion of sperm with aneuploidy [ 67 ]. Novel methods of assessing fertility in male patients with cancer include assessing sperm deoxyribonucleic acid (DNA) methylation patterns [ 68 ] and levels of sperm DNA fragmentation in thawed samples [ 69 ]. Anti-MĂŒllerian hormone (AMH) has been demonstrated as a surrogate marker for testicular damage in mice studies [ 70 ].…”
Section: Sperm Banking For Cancermentioning
confidence: 99%